Approximate calculation model and Gibbs model to determine operating parameters of the sucker-rod pumping system - Moreira de Oliveira, Camylla; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2021)
Sucker- rod pump is the artificial lift method most used in the world and the determination of its operating parameters is extremely important to optimize its performance. Tracking the maximum and minimum rod stress can ensure longer life for the rods and for the entire sucker-rod pumping system (Pons, 2014). The key to the proper description of the pumping system is the appropriate simulation of the rod string’s behavior. This paper utilizes the approximate calculation model, and the Gibbs model to calculate the operating parameters PPRL – Peak Polished Rod Load, MPRL – Minimum Polished Rod Load and PT – Peak Torque of the sucker rod pumping system. The simulation of the Gibbs model were performed using the software SROD® and the data for this paper were obtained from the Petrobras database taken from the TWM® (Total Well Management) software. The results of the simulation are compared with two different pump intake pressures provided by the TWM® software, the pump intake pressure determined from acoustic fluid-level surveys and the pump intake pressure determined from dynamometer pump cards. The results present that for the approximate calculation model, the pump intake pressure from acoustic fluid levels is the most adequate to be used, and for Gibbs model via SROD®, the most suitable pump intake pressure is the one obtained from the analysis of the dynamometer pump cards.
Keywords: artificial lift; rod string; dynamometer pump card; intake pressure; TWM